2018
DOI: 10.1038/s41598-018-28185-4
|View full text |Cite
|
Sign up to set email alerts
|

Early alteration of epigenetic-related transcription in Huntington’s disease mouse models

Abstract: Transcriptional dysregulation in Huntington’s disease (HD) affects the expression of genes involved in survival and neuronal functions throughout the progression of the pathology. In recent years, extensive research has focused on epigenetic and chromatin-modifying factors as a causative explanation for such dysregulation, offering attractive targets for pharmacological therapies. In this work, we extensively examined the gene expression profiles in the cortex, striatum, hippocampus and cerebellum of juvenile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 95 publications
7
41
0
Order By: Relevance
“…This is in agreement with a recent study demonstrating that HD neuronal and glial cells are affected in opposite ways at transcriptional level 50 . Our R6/1 hippocampal transcriptional data showed a great overlap with previously generated data in additional HD models 29,52 and, according to a recent study, these common transcriptional signatures present high homology with those found in knockouts for histone acetyltransferases and methyltransferases 28 . Being shown the interplay between lamin B1 protein levels and H3K9me3, highly dependent on the activity of methyltransferases, it can be speculated that nuclear lamina alterations could play a role in a particular subset of the HD transcriptional signature.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This is in agreement with a recent study demonstrating that HD neuronal and glial cells are affected in opposite ways at transcriptional level 50 . Our R6/1 hippocampal transcriptional data showed a great overlap with previously generated data in additional HD models 29,52 and, according to a recent study, these common transcriptional signatures present high homology with those found in knockouts for histone acetyltransferases and methyltransferases 28 . Being shown the interplay between lamin B1 protein levels and H3K9me3, highly dependent on the activity of methyltransferases, it can be speculated that nuclear lamina alterations could play a role in a particular subset of the HD transcriptional signature.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, we found a substantial overlap with previously identified sets of altered expressed genes in other HD mouse models ( Supplementary Fig. 6f) 28,29 . As expected, we found that only genes showing the highest transcriptional dysregulation (adjusted p value <0.001, |fold change| >2) displayed significant changes in chromatin accessibility at their TSS as compared with genes only filtered according to their adjusted p value ( Fig.…”
Section: Chromatin Accessibility Gene Transcription and Lads Organizsupporting
confidence: 66%
See 1 more Smart Citation
“…While restoring CREB activity in the CA1 of the dorsal hippocampus enables recovery from spatial memory deficits in an amyloid beta model of Alzheimer's disease (29), pharmacological activation of CBP/p300 HAT function also improves spatial learning in wildtype (WT) mice and restores spatial long-term memory retention and hippocampal plasticity in a tauopathy mouse model (30,31). Decreased levels or dysregulation of CBP have also been associated with neurodegenerative diseases including Huntington's Disease (32,33) and Alzheimer's disease (34)(35)(36). Previous research on Alzheimer's disease using rodent models found that decreases in hippocampal CBP activity levels are accompanied by decreased CREB activation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In both human and mouse HD models, down-regulation of specific genes is observed, largely because of decreased transcription from gene promoters (14 -16). As a result, cellular factors that modulate gene expression and chromatin states, such as histone acetyltransferases and lysine deacetylases, have been the subject of intense investigation (17). Moreover, the lysine acetyltransferase CREB-binding protein (CBP) has been found to colocalize with huntingtin inclusions (18), whereas histone deacetylase interaction partners were found to have altered subcellular distribution patterns in HD brains (19).…”
mentioning
confidence: 99%